Ordering international politics : identity, crisis, and representational force - Mattern, Janice Bially (Routledge, 2005)
How do states sustain international order during crises? Drawing on the political philosophy of Lyotard and through an empirical examination of the Anglo-American international order during the 1956 Suez Crisis, Bially Mattern demonstrates that states can (and do) use representational force--a forceful but non-physical form of power exercised through language--to stabilize international identity and in turn international order.